Ex-vivo short-term culture and developmental assessment of Plasmodium vivax. - Chotivanich, K; Silamut, K; Udomsangpetch, R; Stepniewska, K; Pukrittayakamee, S; Looareesuwan, S; White, N (2001)
A simple reproducible method for short-term ex-vivo Plasmodium vivax culture is presented in which glucose, ascorbic acid, thiamine, hypoxanthine, and 50% human AB+ serum are added to the standard P. falciparum in-vitro culture medium. Culture of freshly obtained blood samples from patients with acute vivax malaria with > 0.5% parasitaemia resulted in > 95% complete schizogony. Culture could be continued for 5-6 cycles without the addition of red cells. Criteria for staging the erythrocytic development of P. vivax in the first schizogonic cycle based on synchronous ex-vivo culture are presented. The asexual cycle was divided into 7 morphological stages: tiny ring (0-6 h), small ring (6-12 h), large ring (12-18 h), early trophozoite (18-28 h), late trophozoite (28-36 h), early schizont (36-42 h) and mature schizont (42-48 h). This simple method of culturing P. vivax ex vivo is suitable for antimalarial susceptibility and immunoparasitology studies.